Editorial - García, César Augusto Vásquez (Universidad Santo Tomás, Bogotá, Colombia, 2013)
The monographic number about “historia y cultura del pensamiento latinoamericano” (history and culture in the Latin-American thinking) begins and ends is opened and closed with two articles that locate the Latin-American thinking, both from the history of the ideas’ perspective and from the contemporary politic philosophy; namely: teacher Álvaro Acevedo Gutiérrez in “América: identidad, integración e independencia” (America: identity, integration and Independence) develops systematically the nominal thesis regarding the category of  “lo americano” (America’s own features) and its configuration throughout the XVI to XIX centuries, with special attention on how the gentes de saber (educated people such as Juan Pablo Viscardo y Guzmán, Hipólito de Unanue, Francisco de Miranda, Andrés bello, Fray Servando Teresa de Mier, Félix Varela y Simón Bolívar, among others) understand the existence  and the essence of  “lo americano” from their visions of identity, integration and independence. In the other hand, master Mario Magallón Anaya in the text “El problema del sujeto en la posmodernidad occidental” (the problem of the subject in the occidental postmodernity) questions subjectivity and modern subject as categories, when considering the Latin-American as a being that has become a subject throughout time and through its vindicatory struggles until nowadays, based on frameworks regarding the liberal-democratic tradition, human rights and the political and social movements.